What are the demands of volleyball match-play? A systematic review of the external and internal loads encountered according to playing position, number of sets, and player sex - Rebelo, A.; Stojanovic, E.; Martinho, D. V.; Pérez-López, A.; López-Samanes, Á.; Scanlan, A: T. (Journal of Sports Sciences, 2026)
Although volleyball is widely practiced and researched around the world, no research has performed the fundamental initial step of consolidating findings regarding match-play demands in the sport. Consequently, this systematic review synthesized the available evidence on the external and internal loads experienced by volleyball players during match-play. Studies were included if they reported external and/or internal load data during indoor volleyball match-play for players of any age, sex, or competitive level. PubMed, Scopus, SPORTDiscus, and Web of Science were searched on July 7, 2025, with the methodological quality of included studies assessed using the Observational Study Quality Evaluation tool. Twenty-eight studies were included. Setters performed the greatest jump volumes, while middle blockers and outside/opposite hitters performed the most high jumps (>50 cm). Internal load also varied by position, with middle blockers, liberos, and setters typically reporting the highest perceived exertion (˜5.3 to 7.7 AU across the number of sets played). Females performed more jumps but at lower heights and generally reported higher internal loads than males. This review provides a foundational reference concerning volleyball match loads to guide player monitoring, training, and recovery strategies, while also generating useful recommendations for future research.